PELATIHAN PEMANFAATAN PROBIOTIK UNTUK BUDIDAYA IKAN KERAPU BEBEK (CROMILEPTES ALTIVELIS) DI KERAMBA JARING APUNG DI KABUPATEN PESAWARAN, LAMPUNG - Amiin, Muhammad Kholiqul; Yusup, Maulid Wahid; Winanti, Diki Danar Tri; Saputra, Rizqy Hadi (Universitas Mataram, 2024)
This community service promotes a sustainable and environmentally friendly approach to modern fisheries, benefiting the surrounding community's economy. Probiotic technology applied for cultivating duck groupers in floating net cages at Sari Ringgung Beach, Hanura Village, Teluk Pandan District, Pesawaran. Utilizing probiotics in floating net cages enables fish growth to 3x3x3 m in size, with each cage holding a maximum of 300 fish. The average weight of the harvested fish is 400-500 grams, resulting in a total production of 150 kilograms of fish. The activity collaborated with lecturers from the Program Study of Marine Science, Aquaculture, and Agricultural Product Technology, involving students of the Program Study of Marine Science, and partners of the Bina Usaha II fish farmer group in Ringgung Village. The partners' contribution was to prepare a place for training and manufacturing practices. Activities that the team has carried out include giving pretest and posttest questionnaires, coordinating with partners for tools and materials, and applying probiotics to fish. Thus, duck grouper farmers who use probiotics in floating net cages can minimize the operational costs of cage maintenance and increase survival rates. The application of the technology is supported by the optimization of the aquaculture process so that the production and marketing activities of the products can be increased.